Instrumentation and table setup for septoplasty surgery with turbinectomy - Bedaque, Henrique; Vasconcelos, Lucas Marinho; Gibson, Deborah Carla Santos; Santos, Halan Araújo; Ferreira, Lidiane Maria de Brito Macedo; Guimarães, Maria Luísa Nobre Medeiros e Silva (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Introduction: The success of surgical procedures depends on a set of processes and skills; among them, appropriate surgical instruments and a provision that brings ease and agility to the procedure are an important part of surgery. Objectives: this article seeks to review the nomenclature of usual surgical instruments in septoplasty and turbinectomy surgery, as well as propose a systematic organization of the operating table. Methods: Using images of real instruments individually and in their positions on the instrumentation table, it is sought to make teaching good instrumentation practices didactic. Conclusion: Knowledge about the nomenclature of surgical instruments and their proper organization for the surgery can be a facilitator for a successful procedure.